PENGARUH PEDAGOGICAL CONTENT KNOWLEDGE (PCK) TERHADAP EFIKASI DIRI GURU SEKOLAH DASAR DALAM MENGAJAR IPA - Islami, Kinanti Dyah Nur; Yulistia, Annisa; Astiti, Niken Yuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by variations in elementary school teachers’ selfefficacy in teaching science, which affect the quality of learning. The study aimed to examine the influence of Pedagogical Content Knowledge (PCK) on teachers’ selfefficacy in Metro Barat District. A quantitative approach with an ex post facto design was employed. The population consisted of all elementary school teachers in the district, with a purposive sample of 101 teachers. Data were collected using PCK and teacher self-efficacy questionnaires comprising 34 validated and reliable statements. The data were analyzed using simple linear regression analysis. The findings revealed that PCK had a positive and significant effect on teachers’ selfefficacy, with a contribution of 82.5%. This result implies that higher mastery of PCK strengthens teachers’ self-efficacy in managing and implementing science instruction effectively.